83.2k views
9 votes
Determine formula of the nth term 2, 6, 12 20 30,42​

User Leo Gaunt
by
4.6k points

1 Answer

2 votes

Check the forward differences of the sequence.

If
\{a_n\} = \{2,6,12,20,30,42,\ldots\}, then let
\{b_n\} be the sequence of first-order differences of
\{a_n\}. That is, for n ≥ 1,


b_n = a_(n+1) - a_n

so that
\{b_n\} = \{4, 6, 8, 10, 12, \ldots\}.

Let
\{c_n\} be the sequence of differences of
\{b_n\},


c_n = b_(n+1) - b_n

and we see that this is a constant sequence,
\{c_n\} = \{2, 2, 2, 2, \ldots\}. In other words,
\{b_n\} is an arithmetic sequence with common difference between terms of 2. That is,


2 = b_(n+1) - b_n \implies b_(n+1) = b_n + 2

and we can solve for
b_n in terms of
b_1=4:


b_(n+1) = b_n + 2


b_(n+1) = (b_(n-1)+2) + 2 = b_(n-1) + 2*2


b_(n+1) = (b_(n-2)+2) + 2*2 = b_(n-2) + 3*2

and so on down to


b_(n+1) = b_1 + 2n \implies b_(n+1) = 2n + 4 \implies b_n = 2(n-1)+4 = 2(n + 1)

We solve for
a_n in the same way.


2(n+1) = a_(n+1) - a_n \implies a_(n+1) = a_n + 2(n + 1)

Then


a_(n+1) = (a_(n-1) + 2n) + 2(n+1) \\ ~~~~~~~= a_(n-1) + 2 ((n+1) + n)


a_(n+1) = (a_(n-2) + 2(n-1)) + 2((n+1)+n) \\ ~~~~~~~ = a_(n-2) + 2 ((n+1) + n + (n-1))


a_(n+1) = (a_(n-3) + 2(n-2)) + 2((n+1)+n+(n-1)) \\ ~~~~~~~= a_(n-3) + 2 ((n+1) + n + (n-1) + (n-2))

and so on down to


a_(n+1) = a_1 + 2 \displaystyle \sum_(k=2)^(n+1) k = 2 + 2 * \frac{n(n+3)}2


\implies a_(n+1) = n^2 + 3n + 2 \implies \boxed{a_n = n^2 + n}

User Flegare
by
5.1k points